Cutting force modeling of machining carbon fiber reinforced polymer (CFRP) composites: A review. (1st November 2022) - Song, Yang; Cao, Huajun; Zheng, Wei; Qu, Da; Liu, Lei; Yan, Chunping
Abstract: Carbon fiber reinforced polymer (CFRP) composites have been widely used in high-tech industries due to excellent performances. Because subsequent machining operations, including drilling and trimming, et al., are necessary to meet dimensional or assembly-related requirement, accurate prediction of cutting forces is of great importance to improve tool life and machining quality, which is good for planning and improving machining process of CFRP composites. To explore this issue, the paper gives a detailed review and discussion of the cutting force models, including, mechanistic models; macro-mechanical models; micro-mechanical models and numerical models. Among them, macro-mechanical models are the earliest proposed cutting force models, while mechanistic models are the most studied. This paper predicts and analyzes the future development trend of cutting force models, including variable diversification development for semi-empirical models, study on process-oriented cutting force models, research on cutting mechanisms and study on intelligent manufacturing-oriented cutting force models based on modular development of numerical models.